Adjective + yi dian in Mandarin Chinese and its equivalent in Indonesian language: A contrastive analysis - Wilujeng, Nuning Catur Sri; æ°æœˆ, èŒƒ (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
In the last decade, Mandarin Chinese has been standing as the most studied language as a foreign language. The structure of Mandarin Chinese is not necessarily similar to the grammatical structure of Mandarin Chinese learners. In daily life, structure of different ideas produces different pragmatic functions in the grammar. This article aims to describe the difference between the discourse of